2021
DOI: 10.1016/s2214-109x(21)00209-6
|View full text |Cite
|
Sign up to set email alerts
|

Hospital nurse staffing and patient outcomes in Chile: a multilevel cross-sectional study

Abstract: Background Unrest in Chile over inequalities has underscored the need to improve public hospitals. Nursing has been overlooked as a solution to quality and access concerns, and nurse staffing is poor by international standards. Using Chile's new diagnosis-related groups system and surveys of nurses and patients, we provide information to policy makers on feasibility, net costs, and estimated improved outcomes associated with increasing nursing resources in public hospitals.Methods For this multilevel cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
(30 reference statements)
4
46
0
13
Order By: Relevance
“…Accordingly, a recent scoping review reported that nurses will be under an increased risk for stress, burnout, and depression during the pandemic, where younger female nurses, with less clinical experience, are more vulnerable to adverse mental health outcomes [ 37 ]. Catton and Iro [ 38 ], nurses in WHO and the International Council of Nurses (ICN), recently called for an investment in the augmentation of the nursing profession since the availability of adequate nursing staff can reduce inpatient admissions and hospital stays [ 39 ], a dire situation that most countries are currently facing.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a recent scoping review reported that nurses will be under an increased risk for stress, burnout, and depression during the pandemic, where younger female nurses, with less clinical experience, are more vulnerable to adverse mental health outcomes [ 37 ]. Catton and Iro [ 38 ], nurses in WHO and the International Council of Nurses (ICN), recently called for an investment in the augmentation of the nursing profession since the availability of adequate nursing staff can reduce inpatient admissions and hospital stays [ 39 ], a dire situation that most countries are currently facing.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, considera-se prematuro e até mesmo inocente acreditar que uma única escala/instrumento pode aferir com precisão toda a completude da demanda de trabalho da enfermagem. atividadeS de enfermagem "oCultaS" na aferição da Carga de trabalho Na última década, pesquisadores (3)(4)(5)(25)(26)(27)(28)(29) avançaram na investigação da CTE, inclusive sobre fatores não contemplados nos SCP. A experiência profissional do enfermeiro, por exemplo, pode influenciar no tempo dedicado na admissão de um paciente, independente do nível de complexidade, já que a agilidade e qualidade dessa atividade pode ser favorecida pelas competências adquiridas com o acúmulo da experiência e do desenvolvimento profissional (27) .…”
Section: Sistemas De Classificação De Pacientes: Constituição E Utili...unclassified
“…Tem-se percebido que a complexidade assistencial dos usuários dos hospitais é exponencial, tanto pelo avanço e sofisticação das intervenções diagnóstico-terapêuticas, quanto pela própria transição demográfica e epidemiológica da população, com enfoque no envelhecimento e alta incidência de doenças crônicas, além da elevação dos agravos por causas externas (2) . As atividades da equipe de enfermagem também acompanham essa crescente complexidade, ao passo que constantemente são somadas atribuições para o atendimento da alta demanda assistencial, evidenciando a carga de trabalho da enfermagem (CTE) como uma grande questão na arena de debates da gestão dos serviços de saúde em diferentes cenários socioeconômicos (3)(4)(5)(6) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…One study reported that a high nurse-to-patient ratio was independently associated with a lower risk of in-hospital death in ICU patients [9]. Another study reported that improved hospital nurse staffing was associated with lower inpatient mortality [10]. However, as a predictor of outcomes in HD patients, there has been no research on the relationship between nurse caseload and dialysis patient outcomes.…”
Section: Introductionmentioning
confidence: 99%